Pengaruh Pemberian Ekstrak Etanol Herba Ceplukan (Physalis angulata L.) Terhadap Gangguan Fungsi Ginjal Mencit Putih Jantan - Sri Oktavia; Surya Dharma; Anton Yarman (STIFARM Padang, 2016)
The research on this study aims determine the effect of ethanol extract of Ceplukan to renal impairment of white male mice. This plant has many major content of flavonoid and polyphenol which is an antioxidants.. The study is conducted by five treatments i.e. negative control, positive control, dose 375 mg/kgBW, 750 mg/kgBW, and 1,500 mg/kgBW. All groups were induced by gentamicin for 7 days. Serum creatinin level and renal histopathology is determined on days 8 and 16. Serum creatinine level is analyzed by one way ANOVA statistical analysis. It show that there is significant differences between each group (p˂0,05). Renal histopathology analysis shows at doses 1,500 mg/kgBW there are more widespread expansion of the urinary space, repair of glomerulus cells which is damaged, decrease epithelial cells which is enter into the tubular lumen. It can be concluded that the ethanol extract of ceplukan can repair renal impairment.